The Use Of Celox™ Gauze as an Adjunct to Pelvic Packing in Otherwise Uncontrollable Pelvic Haemorrhage Secondary to Penetrating Trauma. Issue 4 (1st December 2012) - Arul, GS; Bowley, DM; DiRusso, S
Abstract : Haemorrhage from severe pelvic fractures can be associated with significant mortality. Modern civilian trauma centres may manage these injuries with a combination of external pelvic fixation, extra-peritoneal packing and/or selective angiography; however, military patterns of wounding are different and deployed medical facilities may be resource constrained. We report two successful instances of pelvic packing using chitosan impregnated gauze (Celox ™ ) when conventional surgical attempts at vascular control had failed. We conclude that pelvic packing should be considered early in patients with military pelvic trauma and major haemorrhage, as part of damage control surgery and that Celox ™ gauze may be a useful adjunct. In our cases, the Celox gauze was easily removed after 24-48 hours without significant bowel adhesions and did not leave a residual phelgmon (of exudate or gel) that may predispose to infection.